PENGEMBANGAN MODUL PEMBELAJARAN BAHASA INGGRI ESP PROGRAM STUDY TEKNIK LISTRIK JURUSAN ELEKTRO POLINEMA - Aly Imron; Atiqah Nurul Asri; Satrio Binusa Suryadi (Jurnal Akuntansi Bisnis dan Humaniora, 2022)
Changes in the implementation of English learning from semester to semester is a separate problem considering that the content of the material also changes in its emphasis pedagogically. Therefore, research on the development of teaching materials is very relevant to the conditions that occur so that the output later can provide a real contribution to the teaching and learning process. The purpose of this research is to develop English teaching materials that suit the needs of students as well as input from teaching staff as well as available references and documents. This development is very urgent due to changes in the semester of the implementation of the teaching and learning process. Thus, this product is very helpful not only for lecturers, but also students and consequently the availability of a teaching material product. Researchers adapted the Research and Development (R&D) model from Borg and Gall which consisted of 6 stages, namely: (1) initial needs analysis, (2) module development design, (3) creating learning modules, (4) assessment/feasibility testing stage, (5) product trials and (6) learning module refinement stages that produce the final product of development. In conclusion, the availability of teaching modules that can be used in the teaching and learning process.